PENGARUH LAMA INKUBASI LIMBAH PADAT PABRIK KARET PADA MEDIA TUMBUH PEMBIBITAN TANAMAN KAKAO (Theobrama cacao L.) - Wahyudi Wahyudi; Andi Alatas (Jurnal Pertanian UMSB: Penelitian dan Kajian Ilmiah Bidang Pertanian, 2018)
Cocoa plant was an export commodity that contributed in increasing Indonesia'sforeign exchange. For the development of cocoa plants to succeed properly was to prepare planting materials in the nursery well. The purpose of this research was to determine the effect of long incubation of solid waste rubber factory in growing mediaof planting breeding kakao. This research was conducted in Pebaun Hilir Village, Kuantan Mudik district, Kuantan Singingi Regency. The research was conducted for 5 months starting from March to July 2017.The design used in this research is non factorial Randomized Block Design, ie the incubation period of rubber plant solid waste consisting of 5 levels of treatmen,repeated as many as 3 replications so that 15 units of experiment were obtained. Each experimental unit consisted of 4 plants, 3 of which were used as sample plants. The treatment was as follows: S1: Incubate 1 week before planting, S2: Incubate 2 weeks before planting, S3: Incubate 3 weeks before planting, S4: Incubate 4 weeks before planting, S5: Incubate 5 weeks before planting.The observational data were analyzed statistically and continued with the Brightness Advanced Test (BNJ) at 5% level. The parameters observed were: Plant height (cm), stem diameter (cm), number of leaves (strands), leaf area (cm). The long treatment incubation of solid waste rubber factory had an effect on observation parameter of plant height (42,7 cm) length of incubation 1 week before planting, number of leaf (16,4 strands) incubation length 1 week before planting.Keywords: waste incubation, growth of cocoa.